Toxic effects of chlorpyrifos, cypermethrin and glyphosate on the non-target organism Selenastrum capricornutum (Chlorophyta) - Fernandez, Carolina (2020)
The toxic effects of the insecticides chlorpyrifos and cypermethrin, and the herbicide glyphosate on the growth, biovolume and ultrastructure of the green microalgae Selenastrum capricornutum were evaluated. Concentrations between 9.37-150 mg L-1 of chlorpyrifos, 3.12-100 mg L-1 of cypermethrin and 4.7-60 mg L-1 of glyphosate were assayed along with a control culture. The assayed concentrations were prepared using commercial formulations. After 48 h all tested concentrations of the three pesticides reduced significantly the population growth. The 96 h effective concentration 50 (EC50) was 14.45 mg L-1 for chlorpyrifos, 12.37 mg L-1 for cypermethrin and 15.60 mg L-1 for glyphosate. Cells exposed to the three pesticides showed an increase in the cellular size related to the increase in pesticide concentration and exposure time. The most signiﬁcant damages observed on the ultrastructure of cells exposed to the three pesticides included thylakoids and mitochondria disruption, formation of electrodense bodies, accumulation of lipids and increase in the size and number of starch granules. The present study demonstrates that the effects of pesticides also extend to non-target organisms having significant ecological implications.